The Greek Immigration to the United States: Yesterday and Today - Michopoulos, Aris (Études helléniques / Hellenic Studies, 2013)
This paper deals with the topic of Greek Immigration to the United States from the 16th century to today. Its focus, however, is the 1900-1924 and the 1965-today period. Both 1924 and 1965 are two landmarks, since the first one drastically limited immigration, while 1965 opened it up. The second major immigration wave (1965-1980) brought about 150,000 Greeks to America. There is a marked drop in immigration after 1980, continuing to this day. The paper also examines and juxtaposes the living standards and achievements of the early immigrants to those after 1965. Finally, the paper examined the immigration during the last thirteen years and especially the period after the crisis (2010) in Greece. Paradoxically, it found no significant change. The paper explored various avenues to explain this finding. These include: the full membership of Greece into the EEC, the change in its living standards after 1980, its non-existent population growth lately, and finally the possibility of a “masked immigration” that takes the form of “tourists”, students and scientists.